Plans of the Great Powers and Anti-Axis Action of Yugoslav and Bulgarian Agrarian Parties in the Balkans (1940–1941) - Antić, Dejan D. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Before and during the Second World War, there was a strong connection between members of the Agrarian Party (Yugoslavia) and the Bulgarian Agrarian National Union (Bulgarian Agrarian Party). The aforementioned political groups formed a bloc that, with its actions in the Balkans, openly opposed the increasingly pronounced Nazi expansion in Europe. Although divided by political strife, the Yugoslav and Bulgarian agrarian groups stood on distinctly pro-British and anti-German positions on the eve of the Second World War. Considering the importance of their anti-Axis actions, the work reconstructs the events and processes that led to the deepening of cooperation between Yugoslav and Bulgarian agrarians based on available sources and literature. Special attention was paid to the plans of the great powers, primarily Great Britain, towards the Balkan states during 1940 and the beginning of 1941.